Book Reviews: CBT for Those at Risk of a First Episode Psychosis: evidence-based psychotherapy for people with an "At Risk Mental State" – Erratum. Issue 3 (17th March 2015) - Collinson, C.
Abstract : Please note the author of this book review is Dr Catherine Campbell, Clinical Psychologist, Institute of Psychiatry, Psychology and Neuroscience, Kings College London, and not Collinson, C. (2015) as cited in the original article. The book review editors extend their sincere apologies to Dr Campbell for this error.